2013
DOI: 10.1016/j.bbrc.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced inhibition of transcription of tlr4 in vitro is reversed by dexamethasone and correlates with presence of conserved NFκB binding sites

Abstract: Engagement of Toll-like receptor 4 (TLR4) by lipopolysaccharide (LPS) is a master trigger of the deleterious effects of septic shock. Horses and humans are considered the most sensitive species to septic shock, but the mechanisms explaining these phenomena remain elusive. Analysis of tlr4 promoters revealed high similarity among LPS-sensitive species (human, chimpanzee, and horse) and low similarity with LPS-resistant species (mouse and rat). Four conserved nuclear factor kappa B (NFκB) binding sites were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Moreover, the NF‐κB signal pathway which was correlated with inflammatory response is significantly enriched by the GO analysis. Studies have identified that NF‐κB could bind to TLR4 and NLRP3 promoter region, suggesting the transcriptional regulation of NF‐κB on TLR4 and NLRP3 and its downstream targets . Furthermore, melatonin could suppress NF‐κB‐dependent pro‐inflammatory mediators in various cell types .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NF‐κB signal pathway which was correlated with inflammatory response is significantly enriched by the GO analysis. Studies have identified that NF‐κB could bind to TLR4 and NLRP3 promoter region, suggesting the transcriptional regulation of NF‐κB on TLR4 and NLRP3 and its downstream targets . Furthermore, melatonin could suppress NF‐κB‐dependent pro‐inflammatory mediators in various cell types .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome, a group of protein complexes, functions as a sensor to detect danger signals and induces secretion of potent pro-inflammatory cytokines that contribute to obesity-associated chronic inflammation conditions ( 3 , 39 , 40 ). The NF-κB signal pathway which was correlated with inflammatory response and has been identified binding to NLRP3 promoter and transcriptional regulating NLRP3 and its downstream targets ( 41 , 42 ). In this study, we determined that Hoxa5 may take part in the regulation of NLRP3 inflammasome by modulating the NF-κB signal in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…LPS and GCs trigger different, sometimes opposite, signaling pathways. Activated GR interferes with the transcriptional activation function of nuclear factor kappa b (NFkB) 36 , while LPS induces the phosphorylation and translocation of NFkB to the nucleus 37 . GCs activate a phosphatase, responsible for the de-activation of mitogen activated protein kinase (MAPK) pathway 38 while LPS activates the MAPK pathway 39 .…”
Section: Discussionmentioning
confidence: 99%